Da'wah Messages Contained in the World Cup in Qatar - Desy Hendri Yanti; Akhmad Rifa'i (al-Afkar, Journal For Islamic Studies, 2023)
The world cup, which will be held in 2022, is uniquely different from world cups held in the past. This is because of the rules he applies to every individual who wants to enter the country of Qatar, where the world cup is being held for all groups without discrimination. Both from players, as well as spectators and participants who want to enter that country. So this creates a commotion for the players, spectators and participants who want to enter that country. Because this is contrary to what is customary for them, among these regulations is the prohibition of free sex and LGBT relationships. In this research, the author used a descriptive qualitative research method of the library type, namely research that only focused on searching for the data needed in the library literature. The reference sources in this research are divided into two parts, the first is primary sources which include websites that tell directly about the World Cup in Qatar. The two secondary sources include articles, books and several other pieces of literature that are related to the themes raised by the author in this research. The results of the da'wah messages that Qatar applied to the world cup were eight things which included dressing modestly, limiting alcoholic beverages, prohibiting smoking, prohibiting free sex, prohibiting making out in public, prohibiting swearing, prohibiting gambling, prohibiting flags. LGBT